The A10398G Alteration of Mitochondrial ND3 gene in Colorectal Cancer Patients - Bich, Pham Thi; Tu, Nguyen Ngoc; Khuyen, Nguyen Thi; Ha, Do Minh; To, Ta Van; Thai, Trinh Hong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2, 2018)
Abstract: The A10398G alteration of ND3 mitochondrial gene results in an amino acid change from Threonine to Alanine in NADH dehydrogenase 3. The A10398G alteration was shown to be associated with breast cancer and lung cancer. However, there is no data on the frequency and association of the A10398G alteration with pathological characteristics in colorectal cancer. Therefore, this study screened the A10398G in 86 Vietnamese CRC patients and then evaluated the probable association between this alteration and pathological characteristics. A10398G alteration was identified by using PCR-RFLP and DNA sequencing in 50 out of the 86 patients (about 58.1%); among these, the frequency of A10398G alteration in tumor tissue and non-tumor tissue were 54.5% and 56.9%, respectively. A10398G alteration was associated with T-stage of TNM classification (p < 0.05) with 100% of patients in T1 stage bearing A10398G (p<0.05). In contrast, this alteration appeared not to associate with the patients’ age, gender, tumour size, tumour location and lymph node metastases of tumors. Keywords : A10398G alteration, mitochondrial ND3 gene, colorectal cancer, PCR-RFLP, DNA sequencing. References: [1] Arnold, M.SSierra, M. Laversanne, I. Soerjomataram, A.Jemal, F. Bray, Global patterns and trends in colorectal cancer incidence and mortality, Gut 66(4) (2017) 683. [2] http://globocan.iarc.fr/Pages/online.aspx (11/2017). [3] M. Brandon, P. Baldi, D.C Wallace, Mitochodrial mutations in cancer, Oncogen 25 (34) (2006) 4647. [4] C. Aral, O. Ayse, Mitochondrial DNA and cancer, Marmara Medical Journal 20 (2) (2007) 127. [5] http://www.mitomap.org/MITOMAP (11/2017). [6] D. Covarrubias, R.K. Ba, L.J. Wong, S.M. Leal, Mitochndrial DNA variant interactions modify breast cancer risk, J Hum Genet 53(10) (2008) 924. [7] J.A.Canter,A.R. Kallianpur, F.F. Parl, R.C. Millikan, Mitochondrial DNA G10398A polymorphism and invasive breast cancer in African-American women, Cancer Res65(17)(2005) 8028 [8] Nguyễn Thị Tú Linh, Nguyễn Bỉnh Hiếu, Đỗ Minh Hà, Tạ Văn Tờ, Trịnh Hồng Thái, Phân tích biến đổi A10398 ty thể trên bệnh nhân ung thư vú ở Việt Nam, Tạp chí Khoa học ĐHQGHN: Khoa học tự nhiên và công nghệ 31(2) (2015) 36. [9] I. Yuexiao, Yuehua Wei, W. Qiaoli, X. Hui, W. You, Y. Anqi, Y. Hui, G. Yan, Z. Fuxiang,Heteroplasmy of mutant mitochondrial DNA A10398G andanalysis of its prognostic value in non- small cell lung cancer, Oncol Lett12(5)(2016) 3081. [10] AJCC - American Joint Committee on Cancer. Colon and rectum. In: AJCC Cancer Staging Manual. 7th New York, Springer (2010)143. [11] American Cancer Society. Colorectal Cancer facts and figures: 2014-2016. [12] https://blast.ncbi.nlm.nih.gov/Blast.cgi (11/2017). [13] A.M.Czarnecka, T.Krawczyk, M.Zdrozny, J.Lubiński, R.S.Arnold, W.Kukwa, A.Scińska, P.Golik, E.Bartnik, J.APetros, Mitochondrial NADH- dehydrogenase subunit 3 (ND3) polymorphism (A10398G) and sporadicbreast cancer in Poland, Breast Cancer Res Treat 121(2) (2010) 511. [14] T. Chen, J. He, L. Shen, H.Fang, H. Nie, T. Jin, X. Wei, Y. Xin, Y. Jiang, H. Li, G. Chen, J. Lu, Y. Bai, The mitochondrial DNA 4,977-bp deletion and its implication in copy number alteration in colorectal cancer, BMC Med Genet 2350 (2011) 12. [15] J.Lu, L.K. Sharma, Y. Bai, Implications of mitochondrial DNA mutations and mitochondrial dysfunction in tumorigenesis, Cell Research 19(7) (2009) 802. [16] H. Jiang, H.Zhao, H. Xu, L. Hu, W. Wang, Y. Wei, Y. Wang, X.Peng, F Zhou, Peripheral blood mitochondrial DNA content, A10398G polymorphism and risk of breast cancer in a Han Chinese population, Cancer Sci 105(6) (2014) 639.